Solid-state battery with high safety, flame retardance and long cycle performance and production method of solid-state battery

By introducing the second layer of electrolyte of inorganic components into the polymer solid electrolyte, the composite electrolyte is solved, and the shortcomings of gel polymer electrolyte in terms of ionic conductivity, thermal stability and interface stability are achieved, and high safety is achieved , long cycle performance and high temperature adaptability solid-state batteries.

CN119518119AActive Publication Date: 2025-02-25HUIZHOU MARATHON SOLID STATE NEW ENERGY BATTERY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411675214.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The existing gel polymer electrolytes have shortcomings in ionic conductivity, thermal stability and interface stability, resulting in low battery operation efficiency, poor reliability and short service life.

Method used

By introducing a second layer of electrolyte with inorganic components during the preparation of polymer solid electrolyte, a two-layer composite electrolyte is formed, which reduces the crystallinity of the polymer, promotes dissociation of lithium salts, improves conductivity and thermal stability, and enhances the interface stability.

Benefits of technology

It significantly improves the safety performance, flame retardant performance and cycle stability of solid-state batteries, extends the service life of the battery, and improves its application capabilities in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119518119A_ABST
    Figure CN119518119A_ABST
Patent Text Reader

Abstract

The invention provides a solid-state battery with high safety, flame retardance and long cycle performance and a production method thereof, and the production method comprises the following steps: mixing 1, 3-dioxolame, an initiator, a flame retardant, a lithium salt and a solvent to form an electrolyte for later use; the method comprises the following steps: uniformly mixing various lithium compounds, a conductive agent and a binder to form slurry, coating the slurry on an aluminum foil with a protective film, drying to obtain a positive plate, and processing the positive plate and a negative plate through a lamination or winding process to prepare a battery core; a part of the electrolyte solution is injected into the battery core, the humidity is controlled within 20% RH, the pressure is controlled within 1-3 MPa, standing is carried out for 5-8 h at the specific temperature below 60 DEG C to form a first layer of gel, a second layer of electrolyte is added after standing is carried out for 5 h, and then high-temperature treatment, hot pressing and standing are carried out to obtain the solid-state battery. The solid-state battery provided by the invention has relatively high safety and long cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of solid-state battery manufacturing, and in particular to a solid-state battery with high safety, flame retardancy and long cycle performance and a production method thereof. Background Art

[0002] In response to the safety hazards and other problems caused by lithium batteries during use, extensive research has been carried out on solid electrolytes to replace liquid electrolytes. It has significantly improved the safety performance of batteries, which is of great significance in the history of lithium battery development.

[0003] In the prior art, researchers have discovered a variety of solid electrolytes so far, including inorganic solid electrolytes and solid polymer electrolytes.

[0004] Among them, oxide solid electrolytes and hydride solid electrolytes are typical representatives of inorganic solid electrolytes. Polymer solid electrolytes include polymer electrolytes and gel polymer electrolytes.

[0005] Compared with all-solid-state polymer electrolytes, gel polymer electrolytes are considered to be more ideal polymer electrolytes because of their higher ionic conductivity than all-solid-state electrolytes. However, the main problems currently faced by gel polymer electrolytes are: 1. Low ionic conductivity, resulting in low battery operating efficiency and low energy limit, which affects the overall performance of the battery. 2. Low thermal stability: Dehydration, decomposition and melting are prone to problems at high temperatures. These thermal stability issues reduce the reliability and service life of the battery and limit the application of polymer solid electrolytes in high temperature environments. 3. Poor interface stability: The interface between the polymer solid electrolyte and the positive and negative electrode materials is unstable, which can easily cause migration and polarization of the electrolyte. This interface instability will cause the battery performance to decay and affect the battery's cycle stability and service life.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The purpose of the present invention is to provide a method for producing a solid-state battery with high safety, flame retardancy and long cycle performance. The production method introduces a second layer of electrolyte of inorganic components to enhance the polymer solid electrolyte during the preparation process. Through the two-layer composite electrolyte, the crystallinity of the polymer is reduced while promoting the dissociation of lithium salts, thereby improving the conductivity of the polymer electrolyte. In addition, the addition of inorganic components can further improve the thermal stability by enhancing the specific surface area, and enhance the stability between interfaces, thereby reducing the possibility of inducing migration and polarization of the electrolyte.

[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0009] The present invention provides a method for producing a solid-state battery with high safety, flame retardancy and long cycle performance, comprising the following steps:

[0010] Mixing 1,3-dioxolane, an initiator, a flame retardant, a lithium salt and a solvent to form an electrolyte solution for use;

[0011] A plurality of lithium compounds, conductive agents and binders are mixed evenly to form a slurry, which is then coated on an aluminum foil with a protective film, and dried to obtain a positive electrode plate. The positive electrode plate and a negative electrode plate formed by a composite of graphite + carbon silicon are processed into a battery core through a lamination or winding process;

[0012] A portion of the electrolyte solution is injected into the battery core, the humidity is controlled within 20% RH, the pressure is controlled within 1-3MPa, and it is allowed to stand for 5-8 hours at a specific temperature below 60°C to form a first layer of gel. After standing for 5 hours, a second layer of electrolyte including cellulose and inorganic fillers is added, and then high-temperature treatment, hot pressing, and standing are performed to obtain a solid-state battery.

[0013] Through research, it is found that inorganic solid electrolytes have higher electrochemical windows, but inorganic solid electrolytes have larger interface impedance and poor mechanical processing properties. Although polymer electrolytes have good flexibility, they have lower ionic conductivity at room temperature. Therefore, the present invention combines the two to prepare high-performance electrolytes through the definition of specific production methods to solve a series of problems such as low ionic conductivity, poor mechanical strength, and poor interface stability, especially in the second half of the in-situ polymerization, by adding electrolytes containing inorganic components to achieve the enhancement of various aspects of battery performance. The reason why the electrolyte containing inorganic components is added in the second half of the polymerization reaction is that the polymer gel state formed during the in-situ polymerization is initially formed before adding, which can ensure that the first layer of gel has been initially formed, and the addition of the second layer of electrolyte will not affect the gel state of the first layer, and the effect of improving battery performance can be achieved through the composite form of polymer and inorganic components. Therefore, it is found through practice that the timing of adding the second layer of electrolyte is also very important, so that the two layers of electrolyte can form a better composite state without affecting the gel state of each other.

[0014] Therefore, when the specific production process is actually carried out, the prepared electrolyte solution is first loaded into the prepared battery core. After the system undergoes in-situ polymerization to form a gel under specific temperature, humidity and pressure conditions, cellulose and inorganic fillers, which are reinforcing components that form the second layer of electrolyte, are added after standing for more than 5 hours. The purpose is to form a composite two-layer electrolyte by adding inorganic components and gel to reinforce each other, thereby enhancing the electrochemical properties, mechanical properties and flame retardant properties of the electrolyte, so as to improve the overall stability of the battery. After the solid electrolyte is formed, it needs to undergo a series of high-temperature treatments, hot pressing, and standing treatments to achieve the ideal bonding effect.

[0015] The specific temperature in the above production method is generally controlled below 60°C, and more preferably the temperature is controlled between 20-50°C.

[0016] Preferably, the so-called high temperature treatment refers to a high temperature curing treatment to ensure complete curing and stable performance. The recommended curing temperature is 60°C to 90°C. This process can effectively improve the ionic conductivity of the electrolyte and enhance the overall stability of the battery.

[0017] After battery production is completed, the battery should be left at room temperature to promote material stability and performance maturity. The recommended standing temperature is 25°C, and the standing time is sufficient to allow the chemical reaction inside the battery to reach a stable state, thereby ensuring the long-term reliability and performance of the battery.

[0018] In the above scheme, the initiator can be selected from one or more of azobisisobutyronitrile, 1,3,2-dioxazolidinone-2,2-dioxide, azobisisoheptanenitrile, and aluminum trifluoromethanesulfonate.

[0019] The solvent may be selected from one or more of dimethyl carbonate (DMC), ethylene carbonate (EC) or propylene carbonate (PC).

[0020] The flame retardant can be selected from triethyl phosphate, brominated epoxy resin, brominated polystyrene, melamine and the like.

[0021] The lithium salt may be lithium hexafluorophosphate (LiPF 6 ), lithium bis(trifluoromethylsulfonyl)amide (LiFSI), lithium perchlorate (LiClO 4 )

[0022] The positive and negative plates used in the processing and preparation of the battery core are conventional. The various lithium positive electrodes used in the preparation of the positive plates include one or more of lithium iron phosphate, lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide. The binder is one or more of carboxymethyl cellulose, polyacrylic acid and polytetrafluoroethylene. The conductive agent can be conductive graphite or graphene. The coating temperature is preferably controlled at about 25°C. Within this temperature range, the viscosity and fluidity of the coating can reach the best state, promoting the uniform distribution and curing effect of the slurry.

[0023] In the above scheme, the mass ratio between the three components of lithium compound, binder and conductive agent used to prepare the positive electrode plate and the electrolyte solution is preferably controlled at 96:1.5:2.5:0.5. The reason for controlling this ratio is to optimize battery performance and ensure the electrochemical activity and structural stability of the electrode material.

[0024] The components of the second layer electrolyte selected for enhancement preferably specifically include: 6-10 parts by mass of electrolyte solution, 0.1-1 part of cellulose, and 0.2-0.7 part of inorganic filler.

[0025] Preferably, as a further feasible solution, the electrolyte solution comprises 7-9 parts, the cellulose comprises 0.3-0.8 parts, and the inorganic filler comprises 0.3-0.6 parts by weight.

[0026] More preferably, the electrolyte solution is 8 parts, the cellulose is 1.5 parts, and the inorganic filler is 0.5 parts.

[0027] A part of the prepared electrolyte solution is directly injected into the battery core, and the other part is used as a component of the second layer electrolyte to be compounded with cellulose and inorganic fillers and added together.

[0028] When selecting the components of the second layer of electrolyte, the present invention specifically selects to match cellulose, inorganic fillers and electrolyte solution to improve the performance of the battery, because the addition of cellulose can utilize the polar groups on cellulose to complex with lithium ions to achieve ion migration, thereby increasing the migration rate of lithium ions and thus achieving the purpose of improving ion conductivity, and the addition of cellulose can also achieve the effect of improving the mechanical strength of the gel electrolyte, so that it has good mechanical strength after curing, and the addition of inorganic fillers promotes the dissociation of lithium salts by reducing the crystallinity of the polymer, thereby improving the ion conductivity of the electrolyte. Therefore, the reason why the above components are selected as the components of the second electrolyte layer is that each component does not play a single role, but interacts with each other after compounding to achieve the best in terms of thermal stability, conductivity and mechanical properties of the battery.

[0029] Preferably, as a further feasible solution, the inorganic filler is at least one or more of diatomaceous earth and oxide electrolyte, preferably a mixture of diatomaceous earth and magnesium oxide, and the mass ratio of the two is 2:1.

[0030] On the one hand, the addition of inorganic fillers improves the conductivity. On the other hand, if the amount is unreasonable, it may affect the mechanical strength after curing. Therefore, in order to balance the effects of both aspects, the best combination of inorganic fillers is a mixture of diatomaceous earth and magnesium oxide. The reason for choosing diatomaceous earth is that it can use its porous structure to achieve the adsorption of electrolytes, thereby better achieving the effect of improving battery performance. Similarly, its porous structure enhances the specific surface area and porosity, thereby further improving the thermal stability of the electrolyte itself. However, it is necessary to pay attention to its mass ratio with magnesium oxide. The mass ratio of the two is preferably 0.2:1. The reason for designing the dosage in this way is that through specific practice, it is found that if the added diatomaceous earth is too much due to its porous structure, it will affect the mechanical properties of the battery itself, and the gel state cannot reach the best. Therefore, the amount of both needs to be controlled appropriately, especially the amount of diatomaceous earth should not be too large, and the amount of magnesium oxide as an oxide electrolyte with excellent performance can be slightly larger.

[0031] Preferably, as a further feasible solution, the cellulose mainly consists of cellulose acetate propionate and hydroxypropyl methylcellulose;

[0032] Preferably, the mass ratio of the cellulose acetate propionate and hydroxypropyl methylcellulose is (3-7):1, and can also be 4:1, 5:1, 6:1, etc.

[0033] When selecting cellulose, the present invention screened a variety of celluloses and found that after compounding with cellulose acetate propionate and hydroxypropyl methylcellulose, the performance enhancement effect on the battery is the best. In fact, when screening cellulose, since carboxymethyl cellulose is generally used as a binder, experiments were also conducted during the specific experimental process, but it was found that its effect on enhancing the conductivity of the battery is not very good. The reason may be that cellulose acetate propionate and hydroxypropyl methylcellulose can form a long-chain structure after the cellulose is modified. This structure can better improve the gelation ability and thus improve its mechanical properties and conductivity. Therefore, the cellulose that is modified to form a long chain has a better effect. Therefore, through specific experiments, it is found that compounding the above two celluloses in a certain mass ratio can achieve the best effect of improving battery performance.

[0034] Preferably, as a further feasible scheme, the protective film is wet coated on the aluminum foil of the positive electrode, and the protective film is mainly composed of the following components: 6-9 parts of a mixture of graphene and carbon nanoparticles, 0.5-3 parts of a cobalt-chromium alloy powder, and 1-2 parts of a binder, in parts by mass.

[0035] In the process of preparing the protective film of the present invention, the protective film is first coated on the aluminum foil of the positive electrode by a wet process, and then the slurry is coated on the protective film. In the above protective film components, the conductivity and thermal conductivity of the battery itself are improved by compounding the graphene and carbon nanoparticle mixture and the alloy powder particles. The main function of the protective film is to have high conductivity and high thermal conductivity, which can timely conduct away the heat generated by the accumulated current, play a good flame retardant effect, and also achieve a good anti-acupuncture effect. The binder in the above protective film components can be oil-based PVDF.

[0036] Among the components of the above-mentioned protective film, the addition of a mixture of graphene and carbon nanoparticles can achieve the effects of high electrical conductivity and high thermal conductivity on the one hand, and on the other hand, it can be compounded with cobalt-chromium alloy powder to reduce the possibility of thermal runaway of the positive plate, thereby improving the stability and safety of the entire battery, and enhancing the conductivity and service life. The reason why cobalt-chromium alloy powder is used as alloy powder is that cobalt and chromium themselves are not easily oxidized, thereby slowing down the structural changes on the surface of the active material of the positive electrode active material caused by excessive voltage, and improving the stability of the positive electrode material.

[0037] Preferably, as a further feasible solution, the carbon nanoparticles include at least one of carbon nanofibers, carbon nanotubes and nano-carbon powders, preferably a mixture of carbon nanotubes and nano-carbon powders, and the mass ratio of the carbon nanotubes and nano-carbon powders is 1:1.

[0038] Preferably, as a further implementable solution, in the mixture of graphene and carbon nanoparticles, the mass percentage of the graphene is between 50-80%.

[0039] The carbon nanoparticles and graphene are mixed and added together, on the one hand, to play a good role in heat and electricity conduction, and on the other hand, the addition is because the carbon nanoparticles are evenly distributed in the film layer, which reduces the possibility of graphene agglomeration and thus affects the performance, making the interface between the protective film layer and the positive plate more tightly bonded, relieving the internal stress of the film layer, increasing the critical safety thickness of the film layer, and improving the bonding strength between the film layer and the substrate, which is also beneficial to improving the overall mechanical strength of the battery after curing, and can also isolate the positive electrode active material from direct contact with relatively unstable additives and solvents in the electrolyte, thereby improving the overall safety of the battery. In view of the excellent heat and electricity conduction effect of graphene, its mass percentage needs to be higher, and the carbon nanoparticles are preferably added in the form of a composite of carbon nanotubes and nano-carbon powder, with a mass ratio of 1:1, because the mutual matching effect of the two carbon nanoparticles increases the uniformity of the film layer, which is also more conducive to the effect of heat and electricity conduction, and improves the efficiency of heat and electricity conduction.

[0040] In terms of the amount of addition, the amount of cobalt-chromium alloy powder added should not be too large, otherwise the mechanical properties of the battery will fluctuate greatly. Preferably, as a further feasible solution, in the cobalt-chromium alloy powder, the mass proportion of chromium is at least 50% and the total mass proportion of cobalt-chromium is at least 80%. Because the content of cobalt and chromium must be guaranteed in the alloy powder, the amount of the two in the alloy powder is preferably limited according to the above ratio. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] By reading the detailed description of the preferred embodiment below, various other advantages and benefits will become clear to those of ordinary skill in the art. The accompanying drawings are only used for the purpose of illustrating the preferred embodiment and are not considered to be limitations of the present invention. In addition, the same reference symbols are used to represent the same components throughout the accompanying drawings.

[0042] Figure 1 is a diagram showing the internal structure of a solid-state battery prepared in Example 3 of the present invention;

[0043] Figure 2 This is a picture of the internal core pack of the battery of Example 3 of the present invention;

[0044] Figure 3 The process of puncturing and dissecting the solid-state battery prepared in Example 3 of the present invention;

[0045] Figure 4 The results of dissecting the solid-state battery after puncture prepared in Example 3 of the present invention;

[0046] Figure 5 This is the cycle test result of the solid-state battery of Example 3 of the present invention. DETAILED DESCRIPTION

[0047] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0048] Example 1

[0049] The production method of large-capacity solid-state batteries is carried out in the following steps:

[0050] 1) 1,3-dioxolane and triethyl phosphate are dissolved and mixed evenly in a volume ratio of 0.1:1 using a solvent dimethyl carbonate, and then 0.3 mol / L azobisisobutyronitrile and 0.5 mol / L lithium hexafluorophosphate are added and stirred thoroughly to form an electrolyte solution for use;

[0051] 2) 6g of a mixture of graphene and carbon nanoparticles (1.5g of carbon nanotubes, 1.5g of nano-carbon powder, and 3g of graphene), 3g of a cobalt-chromium alloy powder, and 2g of a binder oil-based PVDF are prepared to form a mixed powder, wherein the mass ratio of chromium in the cobalt-chromium alloy powder is 50%, and the total mass ratio of cobalt-chromium is 80%. A certain amount of the prepared mixed powder is taken out according to actual conditions and coated on an aluminum foil using a wet process to form an aluminum foil with a protective film. Then, a lithium compound lithium iron phosphate, a conductive agent conductive graphite, and a binder carboxymethyl cellulose are uniformly mixed to form a slurry, which is coated on the aluminum foil with a protective film. The coating temperature is 25° C. The mass ratio of the lithium compound, the binder, and the conductive agent is 96:1.5:2.5. The positive electrode plate is dried to obtain a positive electrode plate;

[0052] 3) The positive electrode plate coated with the protective film and the negative electrode plate formed by the composite of graphite + carbon silicon are processed into a battery core through a lamination process;

[0053] 4) injecting a portion of the electrolyte solution in step 1) into the battery core, controlling the humidity within 20% RH and the pressure within 1 MPa, and standing for 5 hours at a specific temperature of 20°C to form a first layer of gel, and adding a second layer of electrolyte including cellulose and an inorganic filler to the formed gel after standing for 5 hours, wherein the second layer of electrolyte is prepared by mixing 7g of electrolyte solution, 0.8g of cellulose and 0.3g of diatomaceous earth, and taking out a corresponding amount to add, wherein the cellulose is cellulose acetate propionate and hydroxypropyl methylcellulose in a mass ratio of 3:1, ensuring that the mass ratio of the total mass of the electrolyte solution in the system to the lithium iron phosphate is 0.5:96.

[0054] 5) After adding the second layer of electrolyte, the battery is allowed to stand for 3 hours, and then subjected to high-temperature curing treatment at 90°C, hot pressing, and standing at 25°C, and then the tabs are welded and packaged to obtain a solid-state battery.

[0055] Example 2

[0056] The production method of a solid-state battery with high safety, flame retardancy and long cycle performance is carried out according to the following steps:

[0057] 1) 1,3-dioxolane and brominated epoxy resin are dissolved and mixed evenly in a solvent of ethylene carbonate at a volume ratio of 0.1:1, and then 0.4 mol / L of azobisisoheptanenitrile and 0.5 mol / L of lithium bis(trifluoromethylsulfonyl)amide are added and stirred well to form an electrolyte solution for use;

[0058] 2) 9g of a mixture of graphene and carbon nanoparticles (0.9g of carbon nanofibers, 0.9g of carbon nanotubes, and 7.2g of graphene), 0.5g of a cobalt-chromium alloy powder, and 1g of a binder oil-based PVDF are mixed to form a mixed powder, wherein the mass ratio of chromium in the cobalt-chromium alloy powder is 60%, and the total mass ratio of cobalt-chromium is 85%. A certain amount of the mixed powder is taken out according to actual conditions and coated on an aluminum foil using a wet process to form an aluminum foil with a protective film, and then a lithium compound of lithium nickel cobalt manganese oxide, a conductive agent of conductive graphite, and a binder of polyacrylic acid are uniformly mixed to form a slurry, which is coated on the aluminum foil with a protective film, the coating temperature is 25° C., the mass ratio of the lithium compound, the binder, and the conductive agent is 96:1.5:2.5, and the positive electrode plate is obtained by drying.

[0059] 3) The coated positive electrode plate and the negative electrode plate formed by the composite of graphite + carbon silicon are processed into a battery core through a lamination process;

[0060] 4) injecting a portion of the electrolyte solution in step 1) into the battery core, controlling the humidity within 20% RH and the pressure within 3 MPa, and standing at a specific temperature of 50° C. for 5 hours to form a first layer of gel, and adding a second layer of electrolyte including cellulose and an inorganic filler to the formed gel after standing for 5 hours, wherein the second layer of electrolyte is prepared by uniformly mixing 9 g of electrolyte solution, 0.3 g of cellulose, and 0.6 g of a mixture of diatomaceous earth and magnesium oxide in a mass ratio of 0.2:1, and taking out a corresponding amount to add, wherein the cellulose is cellulose acetate propionate and hydroxypropyl methylcellulose in a mass ratio of 7:1, and ensuring that the mass ratio of the total mass of the electrolyte solution in the system to the mass of lithium iron phosphate is 0.5:96.

[0061] 5) After adding the second layer of electrolyte, the battery is allowed to stand for another 2 hours, and then subjected to high-temperature curing treatment at 60°C, hot pressing, and standing at 25°C, and then the tabs are welded and packaged to obtain a solid-state battery.

[0062] Example 3

[0063] The production method of a solid-state battery with high safety, flame retardancy and long cycle performance is carried out according to the following steps:

[0064] 1) 1,3-dioxolane and trichloromelamine are dissolved and mixed evenly in a volume ratio of 0.1:1 using ethylene carbonate as a solvent, and then 0.4 mol / L of 1,3,2-dioxazolethiophene-2,2-dioxide and 0.5 mol / L of lithium perchlorate are added and stirred well to form an electrolyte solution for use;

[0065] 2) 8g of a mixture of graphene and carbon nanoparticles (1.6g of carbon nanofibers, 1.6g of carbon nanotubes, and 4.8g of graphene), 1g of a cobalt-chromium alloy powder, and 1.5g of a binder oil-based PVDF are prepared to form a mixed powder, wherein the mass ratio of chromium in the cobalt-chromium alloy powder is 60%, and the total mass ratio of cobalt-chromium is 85%. A certain amount of the prepared mixed powder is taken out according to actual conditions and coated on an aluminum foil using a wet process to form an aluminum foil with a protective film. A lithium compound of lithium nickel cobalt manganese oxide, a conductive agent of conductive graphite, and a binder of polyacrylic acid are mixed evenly to form a slurry, which is coated on the aluminum foil with a protective film. The coating temperature is 25° C. The mass ratio of the lithium compound, the binder, and the conductive agent is 96:1.5:2.5. The positive electrode plate is dried to obtain a positive electrode plate;

[0066] 3) The coated positive electrode plate and the negative electrode plate formed by the composite of graphite + carbon silicon are processed into a battery core through a lamination process;

[0067] 4) injecting a portion of the electrolyte solution in step 1) into the battery core, controlling the humidity within 20% RH and the pressure within 2 MPa, and standing at a specific temperature of 40° C. for 5 hours to form a first layer of gel, and adding a second layer of electrolyte including cellulose and an inorganic filler to the formed gel after standing for 5 hours, wherein the second layer of electrolyte is prepared by uniformly mixing 8 g of electrolyte solution, 1.5 g of cellulose, and 0.5 g of a mixture of diatomaceous earth and magnesium oxide in a mass ratio of 0.2:1, and taking out a corresponding amount to add, wherein the cellulose is cellulose acetate propionate and hydroxypropyl methylcellulose in a mass ratio of 6:1, to ensure that the mass ratio of the total mass of the electrolyte solution in the system to the mass of lithium iron phosphate is 0.5:96.

[0068] 5) After adding the reinforcing components, the battery is allowed to stand for 3 hours, and then subjected to high-temperature curing treatment at 70°C, hot pressing, and standing at 25°C, and then the tabs are welded and packaged to obtain a solid-state battery.

[0069] Figure 1 The internal structure diagram of the solid-state battery of this embodiment is shown in FIG. Two samples of the solid-state battery were selected for cycle testing to evaluate their long-term performance. The specific test results are shown in FIG. Figure 5 This test not only verifies the cycle stability of the battery, but also ensures its high performance and long life in practical applications. Figure 3 It can be seen that after the needle puncture test, the battery maintains a high level of safety, with no burning or thick smoke. Figure 4 It can be seen that after the battery is dissected after puncture, the current collector is characterized uniformly and the bonding surface is good. Figure 2 The figure shows the solid-state representation of the battery core pack after the electrolyte solidifies.

[0070] Example 4

[0071] The specific operation steps are the same as those in Example 3, except that: the second layer electrolyte is prepared by uniformly mixing 6 g of electrolyte solution, 1 g of cellulose, and 0.2 g of a mixture of diatomaceous earth and magnesium oxide in a mass ratio of 0.2:1, and then taking out a corresponding amount to add, wherein the cellulose is cellulose acetate propionate and hydroxypropyl methylcellulose in a mass ratio of 6:1.

[0072] Example 5

[0073] The specific operation steps are the same as those in Example 3, except that: the second layer electrolyte is prepared by uniformly mixing 10 g of electrolyte solution, 0.1 g of cellulose, and 0.7 g of a mixture of diatomaceous earth and magnesium oxide in a mass ratio of 0.2:1, and adding a corresponding amount of cellulose, wherein the cellulose is cellulose acetate propionate and hydroxypropyl methylcellulose in a mass ratio of 6:1.

[0074] Example 6

[0075] The specific operation steps are consistent with those of Example 3, except that the mixture of graphene and carbon nanoparticles is replaced by adding only graphene.

[0076] Example 7

[0077] The specific operation steps are consistent with those in Example 3, except that the carbon nanoparticles are only one type of carbon nanofibers.

[0078] Example 8

[0079] The specific operation steps are consistent with those of Example 3, except that: 2 g of graphene, 3 g of carbon nanofibers, and 3 g of carbon nanotubes.

[0080] Example 9

[0081] The specific operation steps are the same as those in Example 3, except that no cobalt-chromium alloy powder is added.

[0082] Example 10

[0083] The specific operation steps are the same as those in Example 3, except that 0.5 g of a mixture of diatomaceous earth and magnesium oxide in a mass ratio of 0.2:1 is replaced with 0.5 g of diatomaceous earth.

[0084] Embodiment 11

[0085] The specific operation steps are consistent with those in Example 3, except that the mass ratio of diatomaceous earth to magnesium oxide is 3:1.

[0086] Example 12

[0087] The cellulose is cellulose acetate propionate.

[0088] Example 13

[0089] The cellulose is prepared by mixing cellulose acetate propionate and hydroxypropyl methylcellulose in a mass ratio of 1:1.

[0090] Experimental Example 1

[0091] The batteries prepared by the production methods of the above-mentioned embodiments and comparative examples were subjected to performance tests. The specific test results are shown in Table 1 below, wherein the first column is the capacity of the battery test after assembly, and the second column is the capacitance retention rate after 500 cycles.

[0092] In addition, an overcharge test was conducted on the batteries of each embodiment: the battery was placed in a battery explosion-proof test box, a DC regulated power supply was used, the output port of the battery was connected to the input port of the DC regulated power supply, the temperature was controlled at 160° C., and the maximum voltage of the battery of each embodiment at which it was overcharged without catching fire or exploding was recorded. The specific results are shown in Table 1 below.

[0093] Table 1 Test results

[0094]

[0095]

[0096] It can be seen from the results in Table 1 above that the batteries assembled in various embodiments are compared in terms of their capacity, the flame retardant properties of the batteries themselves, and their mechanical properties. It is found that embodiment 3 performs best in various performance indicators. Although other embodiments 1-2 and 4-13 can basically pass the puncture test from the perspective of safety, their flame retardant properties, mechanical properties, and electrochemical properties cannot be as good as the various performance indicators of embodiment 3 due to changes in conditions. In particular, the maximum overcharge voltage of embodiment 3 can reach 5V, and the normal battery voltage is 4.4V. Overcharging is definitely prone to fire and explosion. However, the maximum overcharge voltage of the solid-state battery produced by the solution of the present invention can reach 5V without fire and explosion, indicating that it has good flame retardant properties. Therefore, from the perspective of battery stability itself, the effect of embodiment 3 is the best.

[0097] Figure 2-Figure 5 The experimental results of battery acupuncture and charge-discharge cycle of Example 3 are shown. Since the schemes of Examples 2-5 are also controlled within the scope of the scheme of the present invention, it can be seen from the experimental data in Table 1 that the battery capacity results and the mechanical properties and flame retardant properties of the battery itself can also achieve better results. The conclusion drawn from the experimental data of Examples 1-5 is that as long as the batteries produced by the scheme of the present invention are adopted, they can achieve a large capacitance retention rate, have good chemical stability, and have a good gel state. The mechanical properties and flame retardant properties of the produced batteries can also achieve better results.

[0098] By comparing the experimental data of Examples 6-9 with those of Example 3, it is found that the graphene, carbon nanoparticles and cobalt-chromium alloy powder added in the process of coating the protective film are preferably indispensable. If carbon nanoparticles are not added, the uniformity of the film itself will be affected, so the capacitance retention rate of Example 6 itself will be affected. Although the mechanical properties are not greatly affected, the flame retardant properties and capacitance retention rate are greatly affected. Example 7 is because the carbon nanoparticles are not added in a combined manner, so the uniformity of the film is not very good. Example 8 is because the graphene is not added to a better amount, which affects its poor thermal and electrical conductivity. Of course, if the amount of graphene added is too large, it is easier to agglomerate and its uniformity will also be affected. Therefore, the amount of graphene added should not be too high or too low. In addition, the conductivity can be improved after the alloy powder is combined. If it is not added, the conductivity will be affected, so the capacitance retention rate of Example 9 will also be affected.

[0099] Examples 10-13 compare the screening of the components of the second layer electrolyte. From the data of each example, it can be seen that the added diatomaceous earth, magnesium oxide and cellulose are all of specific significance for improving the performance. In Example 10, since magnesium oxide is not added, its conductive performance cannot achieve a better effect, and its mechanical properties will also be affected. In Example 11, since the amount of diatomaceous earth added is too large, the mechanical properties will also be affected. In Example 12, since only one type of cellulose is limited, and in Example 13, since the two types of cellulose are not controlled within a better mass ratio range, the performance of the battery will be affected to a certain extent. Because the above two types of cellulose are found through practice to have better later reinforcement effects, they can better improve the gel ability and thus improve the electrical and mechanical properties. Therefore, it is best to combine them in a certain mass ratio to achieve the best effect.

[0100] In addition, the mechanical properties are represented by the two indicators of tensile strength and elastic modulus because these two indicators are related to the stability of battery use and service life. Good tensile strength means that the battery is not prone to breakage and has better safety and service life, while a good elastic modulus means that the battery has better shape stability and strong resistance to deformation. Of course, the larger the two indicators are, the better. It is just that keeping them as large as possible within the optimal range will improve the mechanical properties of the battery itself. Therefore, the solution of the present invention improves the performance of the entire battery after curing by adopting a two-layer electrolyte composite method.

[0101] Although the present invention has been illustrated and described with specific embodiments, it will be appreciated that many other changes and modifications may be made without departing from the spirit and scope of the present invention. Therefore, it is intended to include all such changes and modifications within the scope of the present invention in the appended claims.

Claims

1. A method for producing a solid-state battery with high safety, flame retardancy and long cycle performance, characterized in that: The steps include: Mix 1,3-dioxolane, an initiator, a flame retardant, a lithium salt and a solvent to form an electrolyte solution for use; A plurality of lithium compounds, conductive agents and binders are mixed evenly to form a slurry, which is then coated on an aluminum foil with a protective film, and dried to obtain a positive electrode plate. The positive electrode plate and a negative electrode plate formed by a composite of graphite + carbon silicon are processed into a battery core through a lamination or winding process; A portion of the electrolyte solution is injected into the battery core, the humidity is controlled within 20% RH, the pressure is controlled within 1-3 MPa, and the battery core is left standing for 5-8 hours at a specific temperature below 60° C. to form a first layer of gel, and after standing for 5 hours, a second layer of electrolyte including cellulose and inorganic fillers is added, and then a solid-state battery is obtained by high-temperature treatment, hot pressing, and standing. Preferably, the specific temperature is between 20-50°C.

2. The production method according to claim 1, characterized in that The second layer electrolyte comprises: by weight, 6-10 parts of electrolyte solution, 0.1-1 parts of cellulose, and 0.2-0.7 parts of inorganic filler.

3. The production method according to claim 1, characterized in that 7-9 parts of electrolyte solution, 0.3-0.8 parts of cellulose, and 0.3-0.6 parts of inorganic filler.

4. The production method according to claim 2, characterized in that: The cellulose is mainly composed of cellulose acetate propionate and hydroxypropyl methylcellulose; Preferably, the mass ratio of the cellulose acetate propionate and hydroxypropyl methylcellulose is (3-7):

1.

5. The production method according to claim 2, characterized in that: The inorganic filler is at least one of diatomaceous earth and oxide electrolyte, preferably a mixture of diatomaceous earth and magnesium oxide, with a mass ratio of diatomaceous earth and magnesium oxide being 0.2:

1.

6. The production method according to claim 1, characterized in that: The protective film is coated on the aluminum foil of the positive electrode by a wet method, and the protective film mainly consists of the following components: 6-9 parts of a mixture of graphene and carbon nanoparticles, 0.5-3 parts of a cobalt-chromium alloy powder, and 1-2 parts of a binder, in terms of mass fractions.

7. The production method according to claim 6, characterized in that: The carbon nanoparticles include at least one of carbon nanofibers, carbon nanotubes, and nano-carbon powders, and are preferably a mixture of carbon nanotubes and nano-carbon powders, with a mass ratio of the carbon nanotubes and nano-carbon powders being 1:

1.

8. The production method according to claim 6, characterized in that: In the mixture of graphene and carbon nanoparticles, the mass percentage of the graphene is between 50-80%.

9. The production method according to claim 6, characterized in that: In the cobalt-chromium alloy powder, the mass proportion of chromium is at least 50%, and the total mass proportion of cobalt-chromium is at least 80%.

10. The production method according to claim 1, characterized in that: The temperature of the high temperature treatment is between 60-90°C.

Citation Information

Patent Citations

  • High-safety lithium manganese iron phosphate battery

    CN106129365A

  • Positive electrode sheet, production method thereof, and lithium ion battery including positive electrode sheet

    CN108448053A

  • High-energy and high-safety lithium ion battery

    CN110890521A

  • Solid-state lithium metal battery based on multi-layer combined electrolyte, and preparation method thereof

    CN112803066A

  • Solid electrolyte, preparation method of solid electrolyte, lithium ion battery and preparation method of lithium ion battery

    CN114300742A

Cited By

  • High-safety lithium battery and preparation method thereof

    CN120834284A